2020
DOI: 10.5530/jyp.2020.12.71
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitude, and Practice of Pharmacovigilance among Healthcare Professionals in Brazil

Abstract: Background: Adverse Drug Events represent a public health problem with high morbidity and mortality rates around the world. Knowledge, attitudes and practices of health professionals toward pharmacovigilance and reporting these events are important factors to promote safe drug therapy use. Objectives: The aim of this study was to evaluate Knowledge, attitudes and practices of health professionals and reporting of Adverse Drug Events by health professionals in Brazil. Methods: across-sectional study with a pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The study's findings showed that the majority of pharmacists were well-versed in the definitions of PV and ADRs. This result is consistent with other studies in Kuwait [ 13 ], Sudan [ 14 ], India [ 15 ], Brazil [ 10 ], Pakistan [ 6 , 16 ], Saudi Arabia [ 32 – 34 ] and UAE [ 17 ]. In opposition to these studies, other previous studies conducted in Ethiopia [ 11 ], India [ 1 ], and Saudi Arabia [ 12 , 35 ] indicated that pharmacists who participated in these studies had a low level of knowledge about PV and ADRs terminology.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The study's findings showed that the majority of pharmacists were well-versed in the definitions of PV and ADRs. This result is consistent with other studies in Kuwait [ 13 ], Sudan [ 14 ], India [ 15 ], Brazil [ 10 ], Pakistan [ 6 , 16 ], Saudi Arabia [ 32 – 34 ] and UAE [ 17 ]. In opposition to these studies, other previous studies conducted in Ethiopia [ 11 ], India [ 1 ], and Saudi Arabia [ 12 , 35 ] indicated that pharmacists who participated in these studies had a low level of knowledge about PV and ADRs terminology.…”
Section: Discussionsupporting
confidence: 93%
“…The questionnaire for this study was developed after reviewing other studies on the same subject extensively [ 1 , 10 , 13 16 , 25 28 ] and after discussion among the co-authors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Japan, PA has been used as a predictor of the development of frailty in participants. Given that frailty represents a vulnerable physiological state, to the extent that PA improves this indicator, it decreases health care and thus polypharmacy [19].…”
Section: Introductionmentioning
confidence: 99%